Soldiers’ competencies in the civilian labour market - Materac, Janusz; Knecht, Zdzisław (Kompetencje żołnierzy zawodowych na cywilnym rynku pracy, 2020)
The paper discusses the concept of ‘competency’. The authors identify the elementary competencies of professional soldiers based on literature and their own pilot studies. They also discuss the use of competencies acquired by soldiers as part of military service (The Amazon Military programme and IBM are used as an example). The example of the Israeli Defense Force (IDF) is given as an incubator of competencies used in a market economy. The analysis of source materials and legal acts, an interview and participant observation are used in the work. Interviews with twenty-six managers of companies employing retired officers were conducted as part of a pilot study in the last quarter of 2019 within the project: “Structural and process determinants of the efficiency of public and economic organizations”, of which the authors are members. The purpose of the article is to examine the use of competences acquired during professional military service on the civilian labour market. The research problem of the work is: what useful competencies do professional soldiers (officers of the Polish Army) have on the civilian labour market? For the purposes of the work, the following hypothesis was formulated: competences acquired as part of military service may be an asset in the civilian market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 146-161
Keywords: competencies; skills; profesional soldiers; kompetencje; umiejętności; żołnierze zawodowi